Green Concrete: Residu Pembakaran Sampah Plastik Dan Tekstil Sebagai Pengganti Sebagian Agregat Halus pada Campuran Beton - Suryan, Viktor; Septiani, Virma; Nurfitri, Meta Amalia; Amalia, Direstu; Silitonga, Evandri; Chandra, Putu Wisnu Ardia; Febriansyah, Adha (Universitas Batanghari Jambi, 2024)
Infrastructures are increasing as the population grows. The demand for building materials from the construction industry is also improving. Building materials like fine aggregates come from nature, such as sand. This research aims to partially replace natural fine aggregates in concrete mixes using plastic waste combustion residues. This research uses an experimental method with a quantitative approach. The test specimens used in this study were 24 pieces with a replacement percentage of 0, 5, 10, and 20% residue. The results of this study show that the average concrete strength for replacement of 0, 5, 10, and 20% is 23.77; 23.15; 19.47; 17.77 Mpa. At 5% replacement of fine aggregate, the percentage of concrete strength reached 97.4% of normal concretes. It can be concluded that concrete strength affects the partial replacement of fine aggregates with residues from the combustion of plastic and textile waste.